Numerical investigation of the simultaneous effect of twisted tape and nanofluid hybrid in shell and spiral tube heat exchanger with a special design - Seyed Hossein Hashemi Karouei; Dheyaa J. Jasim; Mohammad N. Fares; Laith S. Sabri; Ahmed Salah Al-Shati (Case Studies in Thermal Engineering)
To increase thermal efficiency, the use of a carefully designed coil instead of a simple tube significantly increases the efficiency of heat exchangers. This is due to increased fluid dynamics and increased turbulence facilitated by the advanced coil design, making it ideal for space-constrained applications. This study performs a numerical evaluation of the fluid hydrodynamic properties of two separate shell and coil heat exchangers with specialized designs.The fluids analyzed include water-based hybrid nanofluids, specifically Water/MOS2_CuO and Ag-HEG/water, with results comparable to those obtained using pure water. This research comprises Reynolds numbers from 500 to 2000 and is divided into two parts. The first part examines the effect of helical coil geometry and fluid type on the endothermic performance of the heat exchanger, using nanoparticle volume concentrations of φ = 0.3. In the second part, the optimal geometric and fluid model is selected based on the findings of the first part. Following this, the effect of different hybrid nanofluids on thermal performance is evaluated and fluids with volume concentrations of φ = 0.3 are compared with pure water. The findings show that Design [A], with a unique geometry with Water/Ag_HEG nanofluid, achieves the highest efficiency at all investigated Reynolds numbers. The results showed that the thermal efficiency (η) of Designs [A], [B], and [C] has increased by 76, 70, and 50 %, respectively, compared to the Designs [D]. In addition, the second part of the study shows that the thermal efficiency of Water/MOS2_CuO and Water/Ag_HEG nanohybrid fluids have increased by 68 % and 21 %, respectively, at Reynolds number 1000.